TRADISI ZIARAH DI JAWA TENGAH - Hartatik, Endah Sri (Sabda: Jurnal Kajian Kebudayaan, 2011)
This article discusses the ceremony khol in the community in some areas in Central Java, which the Islamic Mataram period covered in the territory of Negara Agung, Mancanegara, and Pasisiran. Khol tradition in this region is associated with the sacred figures deemed instrumental in the spread of Islam and became an important tool in the preservation of the values associated with harmony and mutual cooperation as the cornerstone to developing social solidarity.